STRATEGI KOMUNIKASI PEMASARAN DAN MINAT BELI MAHASISWA UNASMAN DI MEDIA SOSIAL FACEBOOK (STUDI EKSPLORASI TERHADAP ONLINE SHOP) - Sri Yuyun (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to determine the sales strategy and buying interest through Facebook social media related to the sale of products such as fashion among FKIP, FIKOM, FIP and FISIP Unasman students. In this study, ten respondents were facebook users in each of the faculties above. This research is a qualitative descriptive study. The results of the study and discussion show that in terms of product sales on social media Facebook is very dependent on the intensity of publications, especially product uploads. Caution in analyzing prospective buyers is also an important factor in efforts to sell products. Creativity in packaging product content offered is also a key to increasing product sales achievements.